Penyusunan Laporan Keuangan Sederhana untuk Penenun Ulos di Desa Sigaol Kabupaten Porsea - Siallagan, Hamonangan; Hasugian, Christnova; Silalahi, Ignatius Valdo (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Knowing the process of making financial reports and the benefits of these financial reports is one way to increase profits in business. Likewise, in Sigaol Village, Uluan District, Porsea Regency, the fathers are the majority of farmers, and the mothers help with the household economy by weaving ulos. Various types of motifs are available, such as maratur star, hotang yeast, mangiring, tonga tonga, pucca, simarhapisoran, and others. Many mothers who start ulos weaving businesses do not have sufficient knowledge or bookkeeping skills. With this service to the people of Sigaol Village, it is hoped that the Ulos weavers can increase profits from their business by knowing the importance of making financial reports and the process of preparing simple financial reports. This PKM activity is beneficial for ulos weavers. The results show that the perpetrators understand the importance of simple bookkeeping and are able to make simple financial reports.